Multi–chamber oscillating water column wave energy converters and air turbines: A review. (15th October 2018) - Shalby, Mohammad; Dorrell, David G.; Walker, Paul
Summary: The oscillating water column (OWC) is a more common type of wave energy converter (WEC) that has been the subject of the study and development for several decades. Multi–chamber oscillating water column (MC–OWC) devices or arrays have the advantage of being more efficient in energy extraction compared to a single chamber system, particularly in more chaotic sea states. A variety of single and array OWC devices have been proposed and studied on a small–scale, whereas few large–scale devices have been tested under ocean wave conditions. This paper provides a concise review of the current state of MC–OWC device development in laboratory conditions. The review highlights explicitly the main stages of MC–OWC device development for one ongoing study as an example. This review was based on the available information in the literature from 2003 to 2012, in addition, further work is presented as part of the current study at the University of Technology Sydney. This study is from 2015 to 2018. The discussion shows the challenges that a device needs to overcome to be more competitive with other WECs in the global of wave energy converter area.